PENERAPAN SANKSI PIDANA MEMPEKERJAKAN ANAK DI BAWAH UMUR BERDASARKAN PERATURAN DAERAH NOMOR 4 TAHUN 2013 TENTANG PELAYANAN, PENETEAPAN DAN PERLINDUNGAN KETENAGAKERJAAN PROVINSI RIAU DI WILAYAH KOTA PEKANBARU - Muhardi Rais; Erdianto '; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In essence, children are not allowed to work because their time should be used to learn, play, fun, be in peace, get the opportunity and facilities to achieve its goals in accordance with the development of physical, psychological, intellectual and social. But in reality many children under the age of 18 years who has been actively involved in economic activity, child labor, among others in the industrial sector on the grounds of economic pressures experienced by their parents or other factors. Based on this understanding, it is this thesis formulated three formulation of the problem, namely: first, how the enforcement of criminal sanctions For Law Firm or Individuals Employ Minors in Pekanbaru City area? second, what are the obstacles in applying criminal sanctions Regional Regulation No. 4 of 2013 in the city of Pekanbaru a gap for some elements that employ minors?The research method in this study, this type of research is sociological and legal research is descriptive. The research location is in the city of Pekanbaru. Source of data used is primary data source, and secondary. Third, the data collection techniques used were interviews and review of the literature. After the data collected then analyzed qualitatively, then draw conclusions with deduktitf thinking method is to analyze the problems of the general form into special shapes.Keywords : Legal Protection - Child Labor - Pekanbaru